(untitled) (Advancements in Homeopathic Research, 2023)
In today’s era there are different types of scales to assess a particular disease condition. Also going through the process of research for the very first time might be quite cumbersome. The reliability and validity of the scale is an essential aspect in any research study. Also thorough knowledge and understanding of every scale is important for its productive application.